"Life stage dissolution" ("adultification" and "infantilization") and the right to repair: implications for fixing this world - Brisman, Avi (Criminological connections, directions, horizons, 2025)
Hayward (2012, 2013) asserts that the distinctions between adolescence and adulthood have become blurred as late-modern capitalist culture has artificially extended the former and delayed the latter. Hayward introduces the concept of ‘life stage dissolution’ - and its attendant bi-directional processes of ‘adultification’ and ‘infantilization’ - to propose that it is becoming difficult for young people to differentiate and disassociate themselves from the generation immediately ahead of them and vice versa. Previous work by Brisman and South (2015, 2017c) sought to extend Hayward's argument to the realm of environmental harms and concerns. More specifically, such work attempted to illustrate how ‘life stage dissolution’ and the resulting ‘generational mulch’ impede efforts toward environmental protection that might take into account future generations, demonstrating how a perverse form of ‘adultification’ places the onus on youth and absolves adults of responsibility for the future of the planet. The present chapter continues this line of inquiry, arguing that the ‘planned obsolescence’ of certain products (Brisman and South, 2013, 2014; Ferrell, 2013, 2020) combined with the ways in which manufacturers have made it difficult for consumers to repair their devices and equipment (from phones to washing machines to tractors) has infantilized adults - at a time when we need grown-ups to address the climate crisis caused by mining, manufacturing, and other energy-intensive practices. While ‘right to repair’ measures would require manufacturers to let individuals ‘fix their stuff’ and would compel them to sell to consumers and independent repair shops the parts and tools to do so, this chapter asks: what message does it send that we need a movement to restore a seemingly fundamental right that most people do not realize they have lost (the right to repair their own equipment)? What does this say about the possible ‘inflation’ of rights (positing too many rights may lead to their devaluation)? What message do fights over ‘who gets to fix what’ send to kids about what they can repair - and whose responsibility it is?